Konstytucja RP w perspektywie orzecznictwa Europejskiego Trybunału Praw Człowieka: [Constitution of the Republic of Poland in the light of the jurisprudence of the European Court of Human Rights] (Studia Prawnicze / The Legal Studies, 2022)
Przedmiotem artykułu jest analiza roli, jaką w orzeczeniach ETPC w sprawach skierowanych przeciwko Polsce odgrywają przepisy Konstytucji RP. W artykule dowodzę, że przepisy Konstytucji RP są wykorzystywane w orzeczeniach trybunału strasburskiego na trzy sposoby. Po pierwsze, są wskazywane jako element kształtujący ramy krajowego systemu prawnego. Po drugie, są wykorzystywane jako pośrednie źródło prawa i w tych sytuacjach ETPC odwołuje się do interpretacji przepisów konstytucyjnych, dokonanej przez TK. Po trzecie, są wykorzystywane jako bezpośrednie źródło prawa do wykładni przepisów EKPC. W takich sytuacjach ETPC nie uwzględnia ich interpretacji dokonanej przez polski TK i dokonuje quasi-samodzielnie (z uwzględnieniem stanowiska innych organów krajowych) interpretuje przepisy konstytucyjne. Jest to podejście nowatorskie, w ramach którego ETPC stawia się w roli gwaranta realizacji nie tylko praw i wolności zagwarantowanych w EKPC, lecz także gwarancji konstytucyjnych, gdy dochodzi do konkluzji, że nie są one zabezpieczone w wystarczającym stopniu przez organy państwa. The subject of the article is an analysis of the role played by the provisions of the Constitution of the Republic of Poland in the rulings of the European Court of Human Rights in cases against Poland. In the article, I argue that the provisions of the Polish Constitution are used in the judgments of the Strasbourg Court in three ways. Firstly, they are indicated as an element shaping the framework of the national legal system. Second, they are used as an indirect source of law. In these situations, the ECtHR refers to the interpretations of constitutional provisions made by the Polish Constitutional Tribunal. Third, they are used as a direct legal source for the interpretation of the provisions of the Convention. In such situations, the ECtHR makes a quasi - independent interpretation of constitutional provisions, disregarding their interpretation included in the rulings of the Constitutional Tribunal. This is an innovative approach, under which the ECtHR sets itself up as a guarantor of the implementation of not only rights and freedoms guaranteed in the Convention, but also constitutional guarantees, when it comes to the conclusion that they are not sufficiently secured by state organs.